Viability of automation, robotization and intelligent systems in the last-mile delivery: a roadmap for future research - Saraceni, Adriana; Oleko, Rozali; Guan, Lisi; Quintens, Lieven (Transport, 2025)
Cutting-edge technologies in automation, robotization and intelligent systems are emerging in last-mile delivery. However, lacking knowledge on viability is limiting the application and transformation in the final stage of logistics chains. The aim of this article is to identify viable automation, robotization and intelligent solutions and discuss their association for last-mile delivery optimization. This article therefore presents a systematic review of automation, robotization and intelligent solutions, followed by empirical data collected from a workshop with practitioners and representatives of logistic companies, seeking to identify associated opportunities and challenges. The analysis resulted in 3 clusters of innovative solutions discerned upon functional characteristics. Furthermore, the acquired empirical data enabled co-relation from theory and practice to both ensuing opportunities and challenges. By analysing the input by practitioners in the field, we propose internal development and spillover effects as deriving opportunities, technical requirements, and societal concerns as emanating challenges. Based on the diversity of opportunities and challenges associated to each solution, this study proposes a roadmap for future research.